2016
DOI: 10.17140/ortoj-1-105
|View full text |Cite
|
Sign up to set email alerts
|

Are Post-Operative Drains Beneficial in Total and Reverse Total Shoulder Arthroplasty?

Abstract: CitationErickson BJ, Campbell K, Jain A, et al. Are post-operative drains beneficial in total and reverse total shoulder arthroplasty?. ABSTRACTBackground: Total shoulder arthroplasty (TSA) and reverse total shoulder arthroplasty (RTSA) are effective treatments for glenohumeral arthritis and rotator cuff arthropathy. Purpose: To determine if the use of a post operative closed-suction drain following TSA and RTSA affects hemoglobin levels, clinical outcomes, and complications. Hypothesis: Patients who did not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…39,45,48,53 However, it has since been shown that drains provide may provide limited benefit and actually increase complications. 89 Lastly, indications are constantly expanding, and occasionally contracting, for various procedures in orthopedic surgery, and we feel it should be noted that RTSA is no longer reserved for those >70 years of age, as some of the top 50 articles recommend. 2,44,45 Similar to sentiments expressed by Namdari et al, we believe quantifying the top 50 most-cited articles in RTSA can provide orthopedists, from new residents to experienced attending shoulder surgeons, with a helpful "short-list" of articles that can orient the reader to the current status and evolution of the body of RTSA literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39,45,48,53 However, it has since been shown that drains provide may provide limited benefit and actually increase complications. 89 Lastly, indications are constantly expanding, and occasionally contracting, for various procedures in orthopedic surgery, and we feel it should be noted that RTSA is no longer reserved for those >70 years of age, as some of the top 50 articles recommend. 2,44,45 Similar to sentiments expressed by Namdari et al, we believe quantifying the top 50 most-cited articles in RTSA can provide orthopedists, from new residents to experienced attending shoulder surgeons, with a helpful "short-list" of articles that can orient the reader to the current status and evolution of the body of RTSA literature.…”
Section: Discussionmentioning
confidence: 99%
“…39,45,48,53 However, it has since been shown that drains provide may provide limited benefit and actually increase complications. 89 Lastly, indications are constantly expanding, and occasionally contracting, for various procedures in orthopedic surgery, and we feel it should be noted that RTSA is no longer reserved for those >70 years of age, as some of the top 50 articles recommend. 2,44,45…”
Section: Discussionmentioning
confidence: 99%
“…The use of drains in total joint arthroplasty has been heavily examined in hip and knee replacements; however, there is a paucity of literature examining effects of drains in shoulder arthroplasty. A study by Erickson et al 10 compared patients who underwent TSA and RTSA with and without a closed suction drain, finding that patients who received closed suction had a greater hemoglobin loss. However, the authors did not compare the extent of blood loss between TSA and RTSA.…”
Section: Discussionmentioning
confidence: 99%